Evaluation of API Coryne system for identifying coryneform bacteria. Issue 8 (August 1994) - Soto, A; Zapardiel, J; Soriano, F
Abstract : AIM--To identify rapidly and accurately coryneform bacteria, using a commercial strip system. METHODS--Ninety eight strains of Corynebacterium species and 62 additional strains belonging to genera Erysipelothrix, Oerskovia, Rhodococcus, Actinomyces, Archanobacterium, Gardnerella and Listeria were studied. Bacteria were identified using conventional biochemical tests and a commercial system (API-Coryne, BioMèrieux, France). Fresh rabbit serum was added to fermentation tubes for Gardnerella vaginalis isolates. RESULTS--One hundred and five out of the 160 (65.7%) organisms studied were correctly and completely identified by the API Coryne system. Thirty five (21.8%) more were correctly identified with additional tests. Seventeen (10.6%) organisms were not identified by the system and three (1.9%) were misidentified. CONCLUSIONS--The system was a good alternative for identification of coryneform organisms. When occasionally performed with some additional tests, this method permits reliable and rapid identification of coryneform organisms compared with conventional methods.